Persepsi Warga Jemaat Gkmi Pulo Gebang terhadap Model Pendidikan Agama Kristen Anak Remaja Berbasis Homeschooling - Yakobus Kristiyono (Departement of Mathematics Education, 2023)
The teenage years are a period of transition with various dynamics of life and development taking place within it. The family, as the primary place and educator for children, plays an important role in determining the learning model that is appropriate for the needs of teenage children. The issue is that the father has not yet developed an optimal pattern of religious upbringing. This is the purpose of this study to describe the Christian educational model for children aged 16-18 years who are homeschooled. This research used the qualitative method with the data analysis stage of collaizzi. Informants were chosen using purposive sampling, with a total of 12 church members. The research was conducted at Gereja Kristen Muria Indonesia Pulo Gebang, Komplek Pertokoan Pulo Gebang Permai blok F19-20, Cakung, Jakarta Timur 15930. The research results showed that homeschooling based on Christianity is a creative and effective learning model that needs to be implemented in families as an effort to overcome the less than optimal implementation of Christianity in both formal and informal education institutions and to improve the quality of education for teenagers.